Reading English Texts in Primary School – Challenges and Shared Experience - Петкова, Десислава (Научни трудове, 2023)
Reading is one of the basic skills that each child has to cover while in school. But there are some other skills that each child has to master before starts reading. In this article I will focus on the pre-reading skills, how to use them and how to make reading fun and easy for the children in primary school. They are all easy and fun to use, but I will focus on the problem that we do not have enough time to use them in state schools and what we can do to implement them in our classes.